Plant and Soil Function Increase With Larger and Older Coarse Woody Debris - Max Mallen‐Cooper; Millie Vernon; David J. Eldridge (Global Ecology and Biogeography, 2026)
Aim Coarse woody debris is increasingly being used in ecological restoration. We aimed to assess the global impacts of woody debris on ecosystem properties and functions. Location Global. Major Taxa Studied Soil biota, plants, soil function. Methods We conducted a quantitative global meta‐analysis of 66 studies (5234 observations) to assess how woody debris influences ecosystem health and specific ecological components, focusing on soil properties, soil biota, and plants. Results Woody debris significantly enhanced soil function, biodiversity, and the abundance of biota. The positive impact on diversity and abundance increased with debris size, and in the case of abundance, age of debris. Most individual attributes such as soil carbon, soil nitrogen, soil infiltration, and the abundance and diversity of microbes, invertebrates, and plants, were enhanced by the addition of woody debris, and generally to a greater extent when the debris was larger and older. Main Conclusions Our results suggest that larger and older pieces of woody debris are more likely to promote ecological functioning and biodiversity.